Management of Moderate to Severe Psoriasis in Patients with Metabolic Comorbidities - Gisondi, Paolo; Galvan, Arturo; Idolazzi, Luca; Girolomoni, Giampiero (Frontiers in Medicine, 2015)
Psoriasis is a chronic inflammatory skin disease affecting 2-3% of worldwide population. The extent of skin involvement is variable, ranging from a few localised plaques to generalised involvement. Moderate to severe psoriasis (>10% of body surface area) is frequently associated with psoriatic arthritis and metabolic diseases, like abdominal obesity, diabetes, nonalcoholic fatty liver disease, dyslipidemia, metabolic syndrome and chronic kidney disease. A common genetic background as well as several acquired risk factors links psoriasis to comorbidities. From a clinical prespective, the understanding of the patients in the context of these comorbidities is very important to ensure that treatment is tailored to meet the individual patient needs. Indeed, some pharmacological treatments may negatively affect cardio-metabolic comorbidities, and have important interactions with drugs that are commonly used to treat them. Non-pharmacological intervention such as diet, smoking cessation and physical exercise could both improve the response to treatments for psoriasis and reduce the cardiovascular risk.